The role of the organizational climate in the application of electronic administration in the faculties of Salahuddin University - Erbil - Mudhafar Hamad Ali ,; Pshtiwan Ahmed Shekh Hamad, (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
This thesis aims to study the role of the organizational climate in the application of electronic administration in the faculties of Salahuddin University - Erbil. The study was applied to the study society represented by the academic leaders of the faculties of Salahuddin University (95) of the deans of the colleges and their assistants and heads of departments. To collect data and information, the questionnaire is used. It sought to test a number of hypotheses related to correlation and influence between the variables of the study, in order to answer the questions related to the problem and reach the goals set. In order to analyze the data, many statistical methods were used, the most important of which were (descriptive statistics, correlation analysis, regression, variance analysis, t test). After analyzing the data statistically, the study reached a number of conclusions, the most important of which is that there is a good harmony between the organizational climate dimensions (organizational structure, communication, technology, participation in decision making, working conditions) and the average compatibility of the requirements of electronic administration Technical, administrative requirements, human requirements, and security requirements) in the responses of the sample members, as well as the existence of significant positive and moral relations between all the dimensions of the five organizational climate (combined and individual) There is a significant effect between the dimensions of the organizational climate (both individually and collectively) as independent variables and electronic management as a dependent variable. These results were consistent with the hypotheses of the study. Based on the findings of the study, the study came out with a number of recommendations, the most important of which are: attention to the organizational climate and review of its dimensions in the faculties of the University of Salah al-Din-Erbil, and work to enhance the positive aspects and address the negative aspects, as this has a major role in promoting the application of electronic administration, As well as providing (necessary technology, material and moral support, training courses, protection programs to ensure the security and safety of administrative information, technical and human resources required)